PENGEMBANGAN SISTEM WEB UNTUK RESERVASI TEMPAT ONLINE DI MADAME HO SKY LOUNGE SEBAGAI SOLUSI OPTIMALISASI PEMESANAN DAN PENGELOLAAN TEMPAT BAGI PELANGGAN - Hilda Fredela Gasendra; Heru Supriyono (Rabit : Jurnal Teknologi dan Sistem Informasi Univrab, 2026)
The restaurant industry is now adopting digitalization to optimize operational management and improve service quality. Madame Ho, an exclusive restaurant with panoramic city views, is a prime destination for activities ranging from private banquets to business meetings. In line with its service vision of offering an intimate dining atmosphere with custom décor, a systematic reservation mechanism is required to ensure timely service. With a limited capacity of seven tables per day, errors in scheduling and an inefficient manual reservation process can potentially lead to irregularities in booking management. These issues highlight the need for a system capable of managing reservations in a more structured manner.This research aims to develop a web-based reservation system that allows customers to select packages, schedule arrival times, and make payments online. The system also features an admin feature for data management (CRUD) and a sales statistics dashboard. Using the Waterfall method, the system was built using HonoJS as the backend, PostgreSQL as the database, and Vercel as the hosting deployment. The system was evaluated using a Black-box Testing approach, confirming that each system feature operated optimally. Furthermore, a System Usability Scale (SUS) test involving 30 respondents yielded a score of 83.58%, placing it in the "Excellent" category within the acceptable range. The results demonstrate that the system effectively improves operational efficiency and simplifies the online reservation process for customers at Madame Ho.